Internal Migration and Integration of Migratory Children in Gymnasiums of Durres - Balla, Nereida (European Journal of Multidisciplinary Studies, 2016)
The aim of this study is to identify the problems that demographic movement has on children of displaced families from rural to urban areas. On this groundwork, the shock on the dimensions of the demographic shift in the level of adjustment is placed as well as children's education displaced to the outcomes of dismissing out of school. Viewed in this perspective, diverse nature of school problems factors and other characteristics that influence this phenomenon are shown. Instructors, students and parents' point of sight is practically brought through methodological argumentation of theoretical and empirical aspects reaching relevant conclusions. This field serves the governing bodies, policymakers and the public to address and improve the adaptation and teaching of this social rank, in prospect of the diversity and achievements in the educational process made by modern standards with all kids. This work concentrates on the variables of family functioning as good as its demographic characteristics, in cooperation with parents and teachers in some views of parent involvement in students' education. Founded on the theory the biological development teenaged Bronfenbrenner (1976), the subject of family environment (interaction of family members with each other) was rated of a great importance to education, in particular the cooperation of school staff with parents. Specifically, this study:- Determines the impact of teacher-parent relationship and vice versa, and in migration or no to the children of displaced families on school spirit.
Keywords: internal migration, migration management, training of children migrates, migrate adaptation of children, domestic migration policies, rates of internal migration and social issues